1996
DOI: 10.1101/gad.10.11.1382
|View full text |Cite
|
Sign up to set email alerts
|

Lef1 expression is activated by BMP-4 and regulates inductive tissue interactions in tooth and hair development.

Abstract: Targeted inactivation of the murine gene encoding the transcription factor LEF-1 abrogates the formation of organs that depend on epithelial-mesenchymal tissue interactions. In this study we have recombined epithelial and mesenchymal tissues from normal and LEF-1-deficient embryos at different stages of development to define the LEF-1-dependent steps in tooth and whisker organogenesis. At the initiation of organ development, formation of the epithelial primordium of the whisker but not tooth is dependent on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
323
3
8

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(347 citation statements)
references
References 49 publications
11
323
3
8
Order By: Relevance
“…In large part, this regulation is achieved at the level of gene transcription, and in recent years, several signaling pathways and transcription factors important for epithelial morphogenesis have been described. These include pathways involving Wnt ligands, ␤-catenin and Lef/Tcf transcription factors (Zhou et al, 1995;Kratochwil et al, 1996;Gat et al, 1998;DasGupta and Fuchs, 1999;Huelsken et al, 2001;Merrill et al, 2001), as well as Shh ligands, and patched and Gli transcription factors (Bitgood and McMahon, 1995;Oro et al, 1997;StJacques et al, 1998;Chiang et al, 1999;Wang et al, 2000). Of interest, the developmental roles of these pathways are conserved from Drosophila to mammals, suggesting the possibility that the function of other regulators involved in developmental control of epidermis in Drosophila may be conserved in mammals (Oro and Scott, 1998;Fuchs et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In large part, this regulation is achieved at the level of gene transcription, and in recent years, several signaling pathways and transcription factors important for epithelial morphogenesis have been described. These include pathways involving Wnt ligands, ␤-catenin and Lef/Tcf transcription factors (Zhou et al, 1995;Kratochwil et al, 1996;Gat et al, 1998;DasGupta and Fuchs, 1999;Huelsken et al, 2001;Merrill et al, 2001), as well as Shh ligands, and patched and Gli transcription factors (Bitgood and McMahon, 1995;Oro et al, 1997;StJacques et al, 1998;Chiang et al, 1999;Wang et al, 2000). Of interest, the developmental roles of these pathways are conserved from Drosophila to mammals, suggesting the possibility that the function of other regulators involved in developmental control of epidermis in Drosophila may be conserved in mammals (Oro and Scott, 1998;Fuchs et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The protein product of this gene is a transcription factor that plays a role in activating Wnt target genes and it is also a critical factor affecting the survival of the epithelial cells during tooth morphogenesis (Sasaki et al 2005). Mice homozygous for the Lef1 deletion died shortly after birth and showed abnormalities in epithelial-mesenchymal interactions, which led to an arrest of tooth development at the bud stage (Kratochwil et al 1996). Defects in odontogenesis were also observed in mice overexpressing Wnt-signaling inhibitors, including Dickkopf and secreted frizzled-related protein 3 (Sarkar and Sharpe 2000;Andl et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…We show here that expression of Lef1 in the MT hair follicles was reduced, suggesting that Smad4 signaling is required for maintaining expression of this gene in the hair shaft progenitor cells. Previous investigations indicated that Lef1 plays an essential role for hair follicle morphogenesis and targeted disruption of Lef1 blocked hair formation (Kratochwil et al, 1996;DasGupta and Fuchs, 1999). We found that, at the end of the first cycle, Smad4 Co/Co MMTV-Cre hair follicle did not contain matrix and precortex cells, leading to the absence of the hair shaft and the IRS in the MT hair follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the Smad4-deficient hair follicles were missing the hair shaft, the IRS and the cortical and medulla cells. We then determined expression of Lef1, an HMG box transcription factor that is Smad4 deficiency results in skin tumor formation W Qiao et al expressed in the hair matrix and the precursor cells of the hair shaft (Figure 4a), and is essential for hair growth (Kratochwil et al, 1996;DasGupta and Fuchs, 1999). In MT mice, we found that Lef1 staining was negative, suggesting the lack of such progenitors in the MT hair follicles (Figure 4b).…”
Section: Smad4-deficient Hair Follicles Did Not Exhibit Normal Differmentioning
confidence: 99%